2010
DOI: 10.1007/s00420-010-0532-4
|View full text |Cite
|
Sign up to set email alerts
|

UV-induced skin cancer at workplace and evidence-based prevention

Abstract: Evidence-based data confirming the benefit of sun protective strategies are scarce, general recommendations are mainly based on the avoidance of UV radiation being identified as potential risk factor for non-melanoma skin cancer in epidemiological studies. Occupational screenings should include regular interventions aimed at enhancing a clear understanding of risk factors for individuals and finally improving the acceptance and maintenance for UV-protective means at workplace.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
57
2
6

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 69 publications
(66 citation statements)
references
References 75 publications
1
57
2
6
Order By: Relevance
“…According to a recent study (17), the risk of developing NMSC is substantially higher for both sexes among outdoor workers in comparison with indoor workers not directly exposed to UV radiation. The vast majority of patients in this study were farmers and rural residents, similar to what was reported in the literature concerning the environmental risk factors for developing NMSC (15,17). Associated with sun exposure, other risk factors may influence the onset of NMSC (1,2,8,9).…”
Section: Discussionsupporting
confidence: 80%
See 2 more Smart Citations
“…According to a recent study (17), the risk of developing NMSC is substantially higher for both sexes among outdoor workers in comparison with indoor workers not directly exposed to UV radiation. The vast majority of patients in this study were farmers and rural residents, similar to what was reported in the literature concerning the environmental risk factors for developing NMSC (15,17). Associated with sun exposure, other risk factors may influence the onset of NMSC (1,2,8,9).…”
Section: Discussionsupporting
confidence: 80%
“…The power of solar radiation depends on many environmental factors, including time of day (higher between 10:00 AM and 4:00 PM), season (higher in the summer), latitude (higher in the tropics), altitude (the higher, the more increased), weather (higher in the absence of clouds) and reflection of radiation (increases in the presence of materials that reflect the sun such as asphalt, water, snow and sand) (1,4,6,15).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[21][22][23] Furthermore, there is no convincing evidence that sunscreen use protects against CMM. Several studies show either no difference in CMM rates between sunscreen users and nonusers or a slight increased risk of CMM in sunscreen users among certain populations.…”
Section: How Sunscreen Can Contribute To Increased Melanoma Incidencementioning
confidence: 99%
“…Several studies show either no difference in CMM rates between sunscreen users and nonusers or a slight increased risk of CMM in sunscreen users among certain populations. [3][4][5][6][7] Although there is convincing evidence that nonmelanoma skin cancer is related to cumulative sun exposure, 6,23 there is less evidence of that association with CMM. If CMM were related to cumulative sun exposure, one would expect that outdoor workers would have a greater incidence of CMM than indoor workers.…”
Section: How Sunscreen Can Contribute To Increased Melanoma Incidencementioning
confidence: 99%